Gcn2 rescues reprogramming in the absence of Hog1/p38 signaling in C. neoformans during thermal stress - David Goich; Amanda L. M. Bloom; Sean R. Duffy; Maritza N. Ventura; John C. Panepinto (mBio)
ABSTRACT The fungus Cryptococcus neoformans is an opportunistic pathogen of humans that reprograms its translatome to facilitate adaptation and virulence within the host. We studied the role of Hog1/p38 in reprogramming translation during thermal stress adaptation and found that this pathway acts on translation via crosstalk with the Gcn2 pathway, a well-studied regulator of general translation control. Using a combination of molecular assays and phenotypic analysis, we show that increased output from the Gcn2 pathway in a Hog1 deletion mutant is associated with rescue of thermal stress adaptation at both molecular and phenotypic scales. We characterize known outputs of the Hog1 pathway during thermal stress as either Gcn2-dependent or Gcn2-independent and demonstrate that Hog1 activation regulates the Gcn2 pathway even in the absence of thermal stress. Finally, we implicate this phenomenon in another Hog1-regulated process, morphogenesis, and recapitulate Hog1–Gcn2 crosstalk in the distantly related fungal pathogen, Candida albicans. Our results point to an important link between the stress response machinery and translation control and clarify the etiology of phenotypes associated with Hog1 deletion. More broadly, this study highlights complex interplay between core conserved signal transduction pathways and the utility of molecular assays to better understand how these pathways are connected.IMPORTANCECryptococcus neoformans is an opportunistic pathogen of humans that causes deadly cryptococcal meningitis, which is is responsible for an estimated 19% of AIDS-related mortality. When left untreated, cryptococcal meningitis is uniformly fatal, and in patients receiving the most effective antifungal regimens, mortality remains high. Thus, there is a critical need to identify additional targets that play a role in the adaptation to the human host and virulence. This study explores the role of the stress response kinases Hog1 and Gcn2 in thermoadaptation, which is a pre-requisite for virulence. Our results show that compensatory signaling occurs via the Gcn2 pathway when Hog1 is deleted, and that disruption of both pathways increases sensitivity to thermal stress. Importantly, our study highlights the insufficiency of using single-gene deletion mutants to study gene function, since many phenotypes associated with Hog1 deletion were driven by Gcn2 signaling in this background, rather than loss of direct Hog1 activity.